Galaxies in the Local Volume - Koribalski, Bärbel Silvia.; Koribalski, Bärbel Silvia.; Jerjen, H.; Jerjen, H. (Astrophysics and Space Science Proceedings,, 2008)
Studies of Nearby Galaxies are currently the focus of many observations and numerical simulations. This book presents an overview of the galaxies within the Local Volume (D < 10 Mpc), including the Local Group (D < 1 Mpc) and our closest neighbours, the Andromeda Galaxy and the Magellanic Clouds. Presented are the latest results from radio, infrared and optical surveys as well as detailed multi-wavelength studies of individual galaxies. Accurate distances are now available for the majority of Local Volume galaxies providing a true 3-dimensional view of their distribution and flow pattern as well as their star formation.